The world is not enough - the value of increasing registry data in idiopathic pulmonary fibrosis - Moor, Catharina; Kreuter, Michael; Luppi, Fabrizio; Wuyts, Wim A. (Respiratory research, 2020)
Idiopathic pulmonary fibrosis (IPF) is a rare, progressive interstitial lung disease (ILD) with a poor prognosis [1]. The treatment landscape for IPF has dramatically changed in the last years [2, 3]. In the last decade, phase III trials have shown the efficacy of anti-fibrotic medication on slowing down lung function decline in IPF [4-7]. Since then, post hoc analyses of these trials have tremendously improved our knowledge about the efficacy of anti-fibrotic drugs across a broad spectrum of lung function impairment, the impact of concomitant medication on disease progression, health-related quality of life, and potential prognostic biomarkers [8-14]. Besides, data from open-label extension studies have informed us about the long-term safety, side-effects and tolerability of anti-fibrotic medication [15, 16]. Nevertheless, it should be noted that these clinical trials included a selected subgroup of patients with IPF, with relatively few comorbidities, strict lung function criteria, and age restrictions [4, 5, 17]. During the last years, an increasing number of IPF disease registries have emerged in order to obtain realworld, long-term data in a broader patient population, complementary to clinical trials. In Europe alone, there are over 90 individual IPF registries by now; a minority also collects data about other ILDs [17]. Patients in registries tend to have a slightly worse health-related quality of life, more clinically important comorbidities, and may have a more severely impaired lung function as compared to patients who participated in clinical trials [18]. Real-world registries have proved to be an important source of information regarding disease behavior, use and long-term efficacy of anti-fibrotic medication, mortality, prevalence and impact of comorbidities, burden of disease, and various other topics [19-23]. Despite these advances, many more essential questions remain to be elucidated in the coming years [17]. Holtze and colleagues recently addressed a few of these questions, by publishing a detailed characterization of IPF treatment patterns in the United States (US), using the Pulmonary Fibrosis Foundation Patient Registry (PFF-PR) [24]. The PFF-PR is a multicenter registry with 42 registry sites across the US, which encompasses data about 1224 patients with IPF enrolled between 2016 and 2018 [24]. With their extensive analysis of different factors associated with anti-fibrotic use, the authors have attempted to gain better insights in the selection process on deciding when to start anti-fibrotic treatment and which type. Strengths of this study include the recruitment of a large number of IPF patients with relatively few missing data. This report is among the first in the US to provide real-world data about prescription habits of anti-fibrotic medication. Data of a specific healthcare system could give us additional insights how particular healthcare systems influence treatment issues in IPF. This study yielded some interesting findings regarding real-world diagnosis and management of IPF in the US [24]. Less than two-thirds (61%) of patients used an antifibrotic drug at the moment of enrollment in the registry or in the twelve months before. Not only in the US, but also in many European countries there is still a significant number of patients in which anti-fibrotic therapy is not initiated, despite a confirmed diagnosis of IPF [25]. Moreover, a substantial minority (23%) of patients were using immunosuppressive medication, which is surprising because the detrimental effects of immunosuppression in